GUARDIÃES DO PARQUE NATURAL MUNICIPAL DOS MORROS (SANTA MARIA, RS, BRASIL): UMA AÇÃO-CONQUISTA A PARTIR DA PERCEPÇÃO AMBIENTAL DOS ESTUDANTES DO ENSINO FUNDAMENTAL - Borgias, Edna Mara da Silva (2022)
This study is part of the research line Teaching and Learning, the Graduate Program in Science Teaching and Mathematics of the Franciscan University, and is dedicated to the Conservation Units of Integral Protection, here, specifically, to the category Municipal Natural Park, called "Parque Natural Municipal dos Morros" (PNMM), located in Santa Maria (Rio Grande do Sul, Brazil). The Park is located in an area of geomorphological and phytoecological transition, between the Atlantic Forest biome and the Pampa biome, with characteristic flora and fauna and endowed with a privileged scenic beauty. Within this context, the objective of the study was to investigate the environmental perception of students of the Municipal Elementary School (EMEF) Teacher Hylda Vasconcellos on the Parque Natural Municipal dos Morros, with a view to developing actions to motivate knowledge about space, foster belonging (action conquest) and its conservation, considering that the school is located in the buffer zone of the Park. As for the methodological design, it is noteworthy that it was a qualitative, exploratory research, case study type, organized to meet the specific objectives established, as well as the participants of the research: students from the final years of elementary school at EMEF Teacher Hylda Vasconcellos, the municipal guard and the PNMM managers. Data collection was performed through interviews, drawings and environmental education activities; and, for the interpretation of the data, Bardin’s Content Analysis (2011) was used. As a result of this study, based on the speeches and conceptions of the Municipal Guard and the Managers, it was found that the PNMM is a space that represents Santa Maria for the ecological relevance and scenic beauty, the diversity of fauna and the possibility of carrying out scientific research and environmental activities. However, it faces obstacles that hinder the management and its conservation as: the lack of human resources prepared to meet the demands, the location of the Park within the urban perimeter, the frequent presence of unauthorized people, the removal of fauna and flora, the invasion of domestic animals, illegal hunting, the practice of sports without respect for standards. As for the perception of students, despite living in the surroundings of the PNMM, most did not know the Conservation Unit or had a partial view about it. Some have a sense of what should be in a Conservation Unit, although partial, and others confused with squares, even with amusement park and a circus. With the development of Environmental Education actions, students were able to know the PNMM since the history of its creation, its beauty, its biodiversity, the pressures that the Park suffers, so they were invited to become “Guardians of the PNMM”. It was noticed the frequency with which the words care, protect, responsibility, preserve and help were written by the students when asked about the mission of being Guardian of the Municipal Natural Park of the Hills. This was the Action-Conquest, expression coined in this work, translated into awareness, stimulation of the perception of the fascinating natural world and threats to its integrity, and engagement in protective actions.